2023
DOI: 10.3389/fpubh.2023.1117709
|View full text |Cite
|
Sign up to set email alerts
|

Stool Xpert MTB/RIF as a possible diagnostic alternative to sputum in Africa: a systematic review and meta-analysis

Abstract: IntroductionWorldwide, COVID-19 pandemic lead to a large fall in the number of newly reported TB cases. In sub-Saharan Africa, microbiological diagnosis of TB is generally based on smear microscopy and Xpert MTB/RIF on sputum samples, but good quality sputum samples are often difficult to obtain, leading clinicians to rely on more invasive procedures for diagnosis. Aim of this study was to investigate pooled sensitivity and specificity of Xpert MTB/RIF on stool samples compared to respiratory microbiological r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Hence, in clinical practice, sequencing results should be strictly interpreted based on patient clinical manifestations in combination with imaging signatures and other conventional clinical microbiological test results. Fifth, it has been shown that stool Xpert MTB/RIF may be a useful rule-in test for children above and below 5 years of age under evaluation for PTB [ 32 ], which is of great significance for patients from whom good quality sputum samples are difficult to obtain. However, the diagnostic value of nanopore sequencing in non-respiratory samples for TB was not explored in this study, which may be our future research direction.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, in clinical practice, sequencing results should be strictly interpreted based on patient clinical manifestations in combination with imaging signatures and other conventional clinical microbiological test results. Fifth, it has been shown that stool Xpert MTB/RIF may be a useful rule-in test for children above and below 5 years of age under evaluation for PTB [ 32 ], which is of great significance for patients from whom good quality sputum samples are difficult to obtain. However, the diagnostic value of nanopore sequencing in non-respiratory samples for TB was not explored in this study, which may be our future research direction.…”
Section: Discussionmentioning
confidence: 99%
“…It is thus essential to, on the one hand, to strengthen existing structures and, on the other, to find alternative solutions. In this regard, recent evidence suggests the possible role of Stool Xpert MTB/RIF on stool samples, especially in sub-Saharan settings, although its diagnostic accuracy and cost-effectiveness are still under investigation [ 12 ]. Despite possible future solutions, it is essential to support and collaborate in defeating TB, not only for low-income countries but also in terms of global and globalised health.…”
Section: Discussionmentioning
confidence: 99%